A Risk Management Analysis on Employee Performance: Literature Review - Widiyanti, Ayu Tri; Hasan, Abdul; Zakiyah, Ana (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Risk management is one of the efforts made to avoid risks or face other risks that can interfere with the achievement of targets, one of the things that can be done is to increase employee performance productivity. The purpose of this study is to determine and analyze the influence of risk management and employee performance in the Company environment. The method used in this literature review uses a comprehensive approach, such as searching for articles in research journal databases, internet searches, and article reviews. The databases used in the search in 2020-2024 include those obtained from Google Scholar with 13,900 articles; PubMed with 1,253 articles, and Science Direct with 6,293 articles. The keywords used in the article search are risk management and employee performance. After identification, screening, and feasibility assessment, ten articles were selected based on the analysis of objectives, topic relevance, research methods used, sample size, research ethics, results of each article, and limitations found. The results of this study, namely the application of risk management to employee performance, are proven to be correct and risk management plays an important role in ensuring the realization of good employee performance in the company.